The volatility of foreign direct investment in Malaysia / Nurasyikin Mohd Shah - Mohd Shah, Nurasyikin (Faculty of Business and Management, 2019)
This study examines the relationship between foreign direct investment (FDI) and the determinants of inflation rate (INR), exchange rate (EXR), gross domestic product (GDP), trade openness (TRO) and infrastructure (INF) from year 1970 to 2017, which contains annual data. This data was analyzed by using Multiple Linear Regressions in order to define the statistical relationship among the variables. Besides using Multiple Linear Regressions, this study also use Descriptive Analysis, and Unit Root Test. In diagnostic checking, some tests done to check the significant presents of autocorrelation, heteroscedascity, the normality of data distribution and model specification. The results of the study shows that there is significant relationship between inflation rate (INR), exchange rate (EXR), trade openness (TRO) and infrastructure (INF) with the foreign direct investment while gross domestic product (GDP) did not have any relationship with the foreign direct investment. As conclusion for the studies shows that INR, EXR, TRO and INF become factor that affecting the foreign direct investment in Malaysia.